Nitrogen amendment of green waste impacts microbial community, enzyme secretion and potential for lignocellulose decomposition. (January 2017) - Yu, Chaowei; Harrold, Duff R.; Claypool, Joshua T.; Simmons, Blake A.; Singer, Steven W.; Simmons, Christopher W.; VanderGheynst, Jean S.
Graphical abstract: Highlights: Thermophilic microbial communities were cultivated on green waste amended with NH4 Cl. Compositions of bacterial and fungal communities and enzyme activities were measured. Relative abundances of genes involved in lignocellulose hydrolysis were predicted. Enzyme and microbial activities were greatest between 5 and 6 wt% nitrogen content. Lignocellulose hydrolysis potential was greatest between 5 and 6 wt% nitrogen content. Abstract: Microorganisms involved in biomass deconstruction are an important resource for organic waste recycling and enzymes for lignocellulose bioconversion. The goals of this study were to examine the impact of nitrogen amendment on microbial community restructuring, secretion of xylanases and endoglucanases, and potential for biomass deconstruction. Communities were cultivated aerobically at 55 °C on green waste (GW) amended with varying levels of NH4 Cl. Bacterial and fungal communities were determined using 16S rRNA and ITS region gene sequencing and PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) was applied to predict relative abundance of genes involved in lignocellulose hydrolysis. Nitrogen amendment significantly increased secretion of xylanases and endoglucanases, and microbial activity; enzyme activities and cumulative respiration were greatest when nitrogen level in GW was between 4.13–4.56 wt% (g/g), but decreased with higher nitrogen levels. The microbial community shifted to one with increasing potential to decompose complex polymers as nitrogen increased with peak potential occurring between 3.79–4.45 wt% (g/g) nitrogen amendment. The results will aid in informing the management of nitrogen level to foster microbial communities capable of secreting enzymes that hydrolyze recalcitrant polymers in lignocellulose and yield rapid decomposition of green waste.